Development of FlipaClip-Based Learning Media to Improve Problem-Solving Skills - Nifrani, Nila; Sutiarso, Sugeng; Firdaus, Rangga; Suningsih, Ari (Universitas Tidar, 2024)
This study aims to evaluate the effectiveness of FlipaClip as a learning media, and to compare the problem-solving abilities of students who learn using FlipaClip and PowerPoint. This study employed the ADDIE development paradigm (Analysis, Design, Development, Implementation, and Evaluate) as a framework for research and development (R&D). The findings demonstrated the validity and viability of learning media that use a contextual approach to linear program content. With extremely valid criteria, the material validation findings came out at 84.38%. The validation results from media experts were 94.79%, which is considered highly valid. Although the student response received an assessment percentage of 83.64%, the response also met the FlipaClip-based learning media's